Fracture risk and height: An association partly accounted for by cortical porosity of relatively thinner cortices. (19th August 2013) - Bjørnerem, Åshild; Bui, Quang Minh; Ghasem‐Zadeh, Ali; Hopper, John L; Zebaze, Roger; Seeman, Ego
ABSTRACT Taller women are at increased risk for fracture despite having wider bones that better tolerate bending. Because wider bones require less material to achieve a given bending strength, we hypothesized that taller women assemble bones with relatively thinner and more porous cortices because excavation of a larger medullary canal may be accompanied by excavation of more intracortical canals. Three‐dimensional images of distal tibia, fibula, and radius were obtained in vivo using high‐resolution peripheral quantitative computed tomography (HRpQCT) in a twin study of 345 females aged 40 to 61 years, 93 with at least one fracture. Cortical porosity <100 µm as well as >100 µm, and microarchitecture, were quantified using Strax1.0, a new algorithm. Multivariable linear and logistic regression using generalized estimating equation (GEE) methods quantified associations between height and microarchitecture and estimated the associations with fracture risk. Each standard deviation (SD) greater height was associated with a 0.69 SD larger tibia total cross‐sectional area (CSA), 0.66 SD larger medullary CSA, 0.50 SD higher medullary CSA/total CSA (i.e., thinner cortices relative to the total CSA due to a proportionally larger medullary area), and 0.42 SD higher porosity (all p < 0.001). Cortical area was 0.45 SD larger in absolute terms but 0.50 SD smaller in relative terms. These observations were confirmed by examining trait correlations in twin pairs. Fracture risk was associated with height, total CSA, medullary CSA/total CSA, and porosity in univariate analyses. In multivariable analyses, distal tibia, medullary CSA/total CSA, and porosity predicted fracture independently; height was no longer significant. Each 1 SD greater porosity was associated with fracture; odds ratios (ORs) and 95% confidence intervals (CIs) are as follows: distal tibia, OR = 1.55 (95% CI, 1.11–2.15); distal fibula, OR = 1.47 (95% CI, 1.14–1.88); and distal radius, OR = 1.22 (95% CI, 0.96–1.55). Taller women assemble wider bones with relatively thinner and more porous cortices predisposing to fracture.